The concept of “demand” and its derivatives in the modern scientific insurance discourse - М. N. Stepanova (Вестник университета)
In the scientific literature concepts such concepts as “demand for insurance”, “demand for insurance services”, “insurance demand”, “demand for insurance products”, etc. are often used. While being simple in their intuitive reading, they are in fact not as unambiguous as they may seem at first glance. Since there is a semantic conditionality of the meaning of a derived word by the values of its components and they are also not always well-established, then terminological uncertainty arises. The negative effect is enhanced by the permissible mixing of concepts with each other or the creation of scholastic multivariability. Quite often, the definition of demand as a category is given a characteristic of the level of demand, and without taking into account its dimension and type. Moreover, there are defects in the choice of definitions and the construction of definitions, the dominance of recursive definitions that have no value for the full disclosure of the meaning and content of the defined. The author concludes about the inadmissibility of taking liberties in the interpretation of significant concepts and terms, careful construction of new turns with their participation. The problem of using concepts without giving meaning to their scientific content is posed.